Safety and efficacy of a platelet glycoprotein Ib inhibitor for patients with non‐ST segment elevation myocardial infarction: A phase Ib/IIa study. Issue 10 (21st September 2021) - Zheng, Bo; Li, Jianping; Jiang, Jie; Xiang, Dingcheng; Chen, Yundai; Yu, Zaixin; Zeng, Hesong; Ge, Junbo; Dai, Xiangrong; Liu, Jiahui; Li, Benjamin; Huo, Yong
Abstract: Study Objective: This study aimed to determine the safety and efficacy of a novel GP Ib receptor inhibitor in patients with non‐ST segment elevation myocardial infarction (NSTEMI) undergoing percutaneous coronary intervention (PCI). Design and Setting: Multicenter, randomized, double‐blind, placebo‐controlled, dose‐escalating, phase Ib‐IIa clinical trial. Eligible patients were randomly assigned to the low‐dose ( n =20, 2 IU/60 kg), moderate‐dose ( n =20, 3 IU/60 kg), or high‐dose anfibatide group ( n =20, 5 IU/60 kg), or the placebo group ( n =30). Anfibatide was administered for up to 48 hours along with standard aspirin and clopidogrel therapy. Patients: Ninety patients with NSTEMI who underwent PCI at six academic hospitals in China. Measurements and Main Results: All three doses of anfibatide showed dose‐dependent antiplatelet activity as measured by ex vivo platelet aggregation at 5 minutes, 24 hours, and 48 hours during infusion, and 4 hours post‐infusion compared with placebo. Higher inhibition of platelet aggregation occurred in all anfibatide groups compared with the placebo group. The post‐procedural TIMI grade flow, myocardial blush grade, and corrected TIMI frame count were not significantly different among the four groups. Thirty‐day mortality, non‐fatal myocardial infarction, and major bleeding were rare and comparable between patients who received anfibatide and placebo. There was no significant difference in the platelet count among the groups during follow‐up. Conclusions: This study shows that intravenous administration of the platelet receptor GP Ib antagonist anfibatide is feasible and safe to inhibit platelet aggregation without increasing the risk of bleeding and thrombocytopenia in patients with NSTEMI undergoing PCI.